2007
DOI: 10.1501/vetfak_0000000266
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of culicoides-borne disease in cattle in European Turkey

Abstract: Summary:In this research, seroprevalence of BTV serotypes (BTV-4, BTV-9, BTV-16), and occurrence of Akabane and Ephemeral fever viruses were investigated in 557 cattle sera collected from 21 locations in European Turkey (Thrace). Virus neutralization test was used to discriminate antibody response against BTV serotypes while commercial blocking-ELISA systems were used to detect antibodies for Akabane and ephemeral fever viruses. The overall seroprevalence of BTV was recorded as 73.54%, comprising individual pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The one in 2008 was limited to the south of the country while the one in 2012 was much wider and spread towards the northwest of the country (Aziz-Boaron et al, 2012;Tonbak et al, 2013;Karayel-Hacıoglu et al, 2021). The serological studies show that, the virus appeared to be circulated in the north and European part of the country (Karaoglu et al, 2007). Reported that, no reported until now of BEFV was obtained from Aegean region located in the west of the country with necessary climate conditions for vectors while a serological study carried out in two provinces in the region found no seropositivity (Erol et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The one in 2008 was limited to the south of the country while the one in 2012 was much wider and spread towards the northwest of the country (Aziz-Boaron et al, 2012;Tonbak et al, 2013;Karayel-Hacıoglu et al, 2021). The serological studies show that, the virus appeared to be circulated in the north and European part of the country (Karaoglu et al, 2007). Reported that, no reported until now of BEFV was obtained from Aegean region located in the west of the country with necessary climate conditions for vectors while a serological study carried out in two provinces in the region found no seropositivity (Erol et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Following the first statement, epidemics were reported to have occurred every 2-4 years in south and southeast regions of Turkey (Aziz-Boaron et al, 2012). The occurring epidemics and serological studies show that the virus is common around middle, south, southeast, north and northwest parts of the country (Karaoglu et al, 2007;Albayrak and Ozan, 2010;Aziz-Boaron et al, 2012;Tonbak et al, 2013;Karayel-Hacıoglu et al, 2021). During all these years, no statement about BEFV has been reported in Aegean region, which is located in the west of Turkey and which has suitable conditions and climate for vector activation.…”
Section: Introductionmentioning
confidence: 98%